Synthesis of Some Novel Substituted Benzaldehyde (Hepta-O-acetyl-β-maltosyl)thiosemicarbazones - Dinh Thanh, Nguyen; Thi Kim Van, Hoang (Asian Journal of Chemistry, 2011)
(Hepta-O-acetyl-β-maltosyl)thiosemicarbazide was synthesized from peracetated β-maltosyl isothiocyanate by reaction with hydrazine hydrate. A series of substituted benzaldehyde (hepta- O-acetyl-β-maltosyl)thiosemicarbazones were synthesized by condensation reactions of (hepta- O-acetyl-β-maltosyl)thiosemicarbazide with corresponding substituted benzaldehydes using microwave-assisted method.